What you know first - MacLachlan, Patricia; Moser, Barry (New York : Joanna Cotler Books, 1995)
As a family prepares to move away from their farm, the daughter reflects on all the things she loves there so that when her baby brother is older she can tell him what it was like.
Keywords: Farm life -- Juvenile fiction; Country life -- Juvenile fiction; Moving, Household -- Juvenile fiction